145k views
5 votes
Rewrite the equation in standard form.
f(x) = 2(x + 3)² - 4

User Kdecom
by
5.0k points

2 Answers

3 votes

Answer:

To rewrite the equation in standard form, you need to expand the parentheses and simplify the equation. To do this, you need to multiply the 2 by the squared term (x + 3)² and then subtract the 4. The equation would then be written as
f (x) = 2x^2 + 12 x -4

User Anjan Bharadwaj
by
5.2k points
2 votes

Answer:
2x^(2)-12x+14

Explanation:


(a+b)^(2) =a^(2)+2ab+b^(2)


2(x-3)^(2)-4=2(x^(2)-2(x)(3)+3^(2))-4=2(x^(2)-6x+9)-4=2x^(2)-12x+18-4=2x^(2)-12x+14

User JohnnyLambada
by
5.4k points